Measurement of dynamic shape factor for particles of various shapes - Chuah, Lawrence Hong Kai. (2010)
The study of particle free settling is important in pulmonary drug delivery systems where the particle shape has a major influence on its terminal velocity. Various shape factors are present in literature to correlate aerodynamic properties of non-spheres to spheres, but dynamic shape factor is the most straightforward for its comparison of drag forces. Dynamic shape factor of a particle is defined as the ratio of drag force experienced by the particle divided by the drag force experienced by a volume-equivalent-sphere settling at the same velocity. Till date, there are little studies that validated the dynamic shape factor values reported by Hinds (1999). In this project, dynamic shape factors for different shapes (sphere, cube, cube-aggregate and cylinder) were calculated based on terminal velocity measurements in transition regime. The velocity measurements were checked for wall effects and only results which gave a wall factor error below 6.3% were considered. The experimental results show an excellent match for dynamic shape factors of sphere and cube when compared with Hinds which were in Stokes regime. However, the experimental value of dynamic shape factor for cylinder with aspect ratio 4 was not close to literature findings. The main reason proposed for this dissimilarity was due to the use of slip correction factor for small particles in Stokes regime with an inadequate shape representation factor to describe cylinder in slip equations. Dynamic shape factors for cube-aggregates and cylinders which were not found in literature were also proposed.